The Design And Development Of Next Generation Learning Spaces (NGLS) Framework In Teachers’ Pedagogy And Technology Tools - Jaya, Sanura (2023)
Malaysian education is rapidly moving toward the digitalization and use of technology in teaching and learning. The new norm demonstrates that secondary school teachers also have to move rapidly toward using technology tools as the main platform in teaching and learning. The main research objectives are to design and develop the NGLS framework, known as oPSTi framework. The framework is developed based on the three phases of the Design Development Research (DDR) approach. The Phase 1 findings showed that the teachers need a proper guideline to understand the concept of technology tools in teachers' pedagogy. The Fuzzy Delphi Method (FDM) analyzes the findings in Phase 2 with 13 experts’ consensus. The 11 accepted elements in the objectives construct involved nine elements in learning spaces, eight for pedagogies strategies and activities, 27 for technology tools, and seven for implementing the oPSTi framework. The accepted elements are based on the expert consensus percentage values ranging from 75% to 100%, and the threshold value is lower than 0.2 (d ≤ 0.2). The defuzzification also showed the value of alpha cut α ≥ 0.5 for the ranking of the accepted elements. The Phase 3 findings also illustrated that all the informants agreed with the aspect of learning spaces, pedagogy, and usability of the technology tools in the oPSTi framework. In conclusion, the results showed strong evidence of the framework's usability and support the transition from traditional learning to next generation learning spaces.